Teacher of Early Childhood Education and formation at a higher level, in Piauí: From ideal to real - Maria Carmem Carmem Bezerra Lima; Luis Carlos Carlos Sales (Universidade Federal de Santa Catarina, 2018)
The aim of this article is to map the teachers who acted in Early Childhood Education, in Piauí, without appropriate initial formation in higher level to act at this stage, starting from the following problematic: Where are the teachers whose initial formation at a higher level does not meet the legal requirements for to play in Early Childhood Education? It is a quantitative study, based on the microdata of the School Census of Basic Education in the year 2013 and is cut out of a Doctorate research in Education. We theoretically on the dictates of Gatti (2004), Kishimoto (2005), Oliveira-Formosinho (2005), Tardif (2007), Oliveira (2011, 2012), Campos et al (2011), among others. We note the existence of 45 courses in different areas working in Early Childhood Education in 2013. The mapping made us conclude that the reality of Early Childhood Education, on the aspect investigated - teacher training - do not suffer major variations of a Management Regional Education (GRE) to another, kept the proper proportions, considering the composition of each run. It is, therefore, a reality very similar.